2023
DOI: 10.3390/pharmaceutics15071839
|View full text |Cite
|
Sign up to set email alerts
|

BRCT Domains: Structure, Functions, and Implications in Disease—New Therapeutic Targets for Innovative Drug Discovery against Infections

Abstract: The search for new therapeutic targets and their implications in drug development remains an emerging scientific topic. BRCT-bearing proteins are found in Archaea, Bacteria, Eukarya, and viruses. They are traditionally involved in DNA repair, recombination, and cell cycle control. To carry out these functions, BRCT domains are able to interact with DNA and proteins. Moreover, such domains are also implicated in several pathogenic processes and malignancies including breast, ovarian, and lung cancer. Although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 132 publications
(216 reference statements)
0
5
0
Order By: Relevance
“…Based on these studies, we generated BRCA1 constructs DBD1 (aa340-554) and DBD2 (aa894-1057). The BRCT domain, known to interact with DNA and proteins involved in DNA repair and recombination [49], was also studied using a BRCT construct (aa1646-1863). Previous studies, while informative, used qualitative methods that did not provide exact DNA binding affinities.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these studies, we generated BRCA1 constructs DBD1 (aa340-554) and DBD2 (aa894-1057). The BRCT domain, known to interact with DNA and proteins involved in DNA repair and recombination [49], was also studied using a BRCT construct (aa1646-1863). Previous studies, while informative, used qualitative methods that did not provide exact DNA binding affinities.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other residues in the α2 helix interact with those in the β4 sheet. The highly conserved residues are located in the central β sheets (β1, β3, β4) and the α1 and α3 helices, whereas the α2 helix shows the greatest variability within the BRCT protein family [ 15 ]. In addition, the β1, α1, α1–β2 loop, β3, α3, and C-terminal end regions contain five conserved hydrophobic motifs, named A, B, C, D, and E, respectively.…”
Section: Structure and Function Of Brca1-brct Domainmentioning
confidence: 99%
“…However, the physiological significance of many such mutations remains unknown due to the lack of BRCT functional assays. Two missense mutations in the BRCT domain were reported in Chinese women with familiar breast cancer, showing similar functions to non-mutated carriers and being associated with reduced growth and stimulated apoptosis [ 15 ]. Previous studies identified six BRCT domain missense mutations (Ser 1655, Val 1696, Arg 1699, Lys 1702, Ala 1708, and Met 1775) that contribute to BRCA1 loss of function and disease through protein-destabilizing effects ( Table 1 ) ( Figure 3 ).…”
Section: Association Of Brca1-brct Domains Mutations and Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, functions of T. brucei RAP1 in telomeric silencing and telomere stability maintenance are intimately involved in the regulation of antigenic variation [52,[103][104][105][106][107], an essential pathogenesis mechanism [108], as the major surface antigen VSG is expressed exclusively from subtelomeric loci [109][110][111][112]. All known RAP1 homologs have an N-terminal BRCA1 C-terminus (BRCT) domain that is frequently identified in proteins involved in the DNA damage response or cell cycle checkpoint [113,114], a central Myb domain that typically binds dsDNA [115,116], and a RAP1 C-terminus (RCT) domain that is a protein-protein interaction domain conserved among all RAP1 homologs [31] (Figure 1). Below, I will discuss RAP1's functions in telomeric silencing and chromosome end protection, focusing on the similarities and differences between TbRAP1 and yeast and mammalian RAP1 homologs.…”
Section: The Telomere Structure and Telomere Functionsmentioning
confidence: 99%